Investigation on mechanical properties of cockle shell composite structure under temperature and aging influence - Anpalagan, Ranjhini (2022)
Cockle shell is one of the marine organisms that can easily found in Malaysia. In this study, a ceramic material was fabricated from cockle shell and used sucrose as a binder. The cockle shell was crushed and milled into small size at around 160 μm -200 μm. The cockle shell powder then was mixed and compacted with sucrose binder by ratio of 10, 20, and 30 wt%. The aim of this project is to find the relationship between cockle shells powder with sucrose binder under influence of drying under oven, room temperature and aging process by months. To find the suitable temperature for the flexural test, compression tests have been done. The samples were placed in an oven at different temperatures of 50°C, 100°C, and 150°C to test the compressive strength. The compression test result shows that the samples with 78wt% of cockle shell at 150°C has the highest strength compare to 68wt%, 88wt% of cockle shells at different temperatures 50°C and 100°C. The drying process was implemented in two methods which heated the samples for an hour at 150°C and another method was the sample placed for drying under room temperature for 24 hours before the flexural test. The effect of binder percentage, drying method and aging process on density, porosity, flexural test, microhardness test, and morphology were investigated. From based on compression test, another set of cockle shell with sucrose binder by same ratio were prepared for flexural test. Density, porosity and flexural test result shows that the samples with oven drying produced better strength compared with samples dried at room temperature for 1 day, 1 month, 3 months and 9 months and the highest strength was obtained by sample with 78wt% cockle shell dried in oven. The finding that integrated, samples with 78wt% of cockle shell at 150°C has the best characteristics under physical and mechanical properties.